PENGARUH USIA HAID PERTAMA ( MENARCHE ) DENGAN USIA MENOPAUSE PADA WANITA USIA 45-60 TAHUN DI PUSKESMAS KWALA BEKALA TAHUN 2018 - Ester Simanullang; Eka F Tarigan; Julianti Lestari (JURNAL ILMIAH KOHESI, 2019)
Background: According to the Word Health Organization (WHO) the average woman experiencesmenopause at the age of 49 years. According to data from the Indonesian Health Data Profile in 2011 thenumber of Indonesians in 2010 was 241,182,182. Adolescents aged 10-19 years amounted to 21,279,177(8.82%) souls and those aged 40-54 years were 20,897,902 (8.66%) souls. From the results of a survey thatI did in February I interviewed 10 respondents. And it turns out that 8 of them experience 9 to 12 years of ageand among them 6 experience 55-60 years of menopause and they admit that when they experience firstmenstruation they feel shocked. And at this time they admitted that they were not comfortable with thesituation. Therefore the authors are interested in researching the effect of menarche age on menopause.Method: The type of research used for this assessment is based on the data and based on the data source.Based on the objectives of this study, it is a correlation study. Results: After being examined from 32respondents, respondents who experienced menarch at the age of 9-12 years predominantly experiencedmenopause at the age of 55 - 60 years as many as 7 people (21.9%). At the age of menarch 3-16 thedominant age experienced menopause at the age of 45 - 49 years as many as 6 people (18.7%). In menarch17-20 years dominant experienced menopause at the age of 45 - 49 years as many as 9 people (28.1%).Conclusion: There is a significant influence between Menarch age and menopausal age experienced by awoman aged 45-60 years in Kwala Bekala Health Center in 2018. (Dr. Eko Budiarto), with p = 0,000 <0.05means Ho is rejected (there are Significant influence between age of menarche and age of menopause).